Different Functions of IbRAP2.4, a Drought-Responsive AP2/ERF Transcription Factor, in Regulating Root Development Between Arabidopsis and Sweetpotato - Bian, Xiaofeng; Kim, Ho Soo; Kwak, Sang-Soo; Zhang, Qian; Liu, Shuai; Ma, Peiyong; Jia, Zhaodong; Xie, Yizhi; Zhang, Peng; Yu, Yang (Frontiers in Plant Science, 2022)
Plant root systems are essential for the uptake of water and nutrients from soil and are positively correlated to yield in many crops including the sweetpotato, Ipomoea batatas (L.) Lam. Here, we isolated and functionally characterized IbRAP2.4, a novel nuclear-localized gene encoding the AP2/ERF transcription factor, from sweetpotato. IbRAP2.4 was responsive to NaCl, PEG8000, ethylene, and Indole 3-acetic acid treatments. As revealed by electrophoretic mobility shift assay and dual luciferase assay, IbRAP2.4 could bind to both DRE and GCC-box elements and acted as a transcription activator. IbRAP2.4 overexpression significantly promoted lateral root formation and enhanced the drought tolerance in Arabidopsis thaliana, while it inhibited storage root formation in transgenic sweetpotato by comprehensively upregulating lignin biosynthesis pathway genes. Results suggested that IbRAP2.4 may be a useful potential target for further molecular breeding of high yielding sweetpotato.